Perturbation-induced nonreciprocal transmission in nonlinear parity-time-symmetric silicon micromechanical resonators - Rui Wang; Lei Han; Man-Na Zhang; Li-Feng Wang; Qing-An Huang (Communications Physics)
Abstract Parity-time (PT) symmetric systems featuring balanced gain and loss, when biased in a broken phase, can produce nonreciprocal transmission in the presence of nonlinear gain. However, the weak coupling in the broken phase leads to high insertion loss during transmission. Here, we demonstrate an approach to achieve nonreciprocal transmission in PT-symmetric silicon micromechanical resonators operating in an exact phase. In our approach, PT-symmetry breaking due to external perturbations to the loss resonator results in exponential growth and decay modes. The presence of the nonlinear gain suppresses the exponential growth mode. As a result, the nonreciprocal transmission is achieved while keeping the system at the strong coupling region. The coupling strength, perturbation, and gain nonlinearity of the system can be electrically tuned. The system shows 8 dB of nonreciprocal transmission with the insertion loss less than 5 dB and the isolation more than 13 dB. Our approach demonstrates the ability to manipulate nonreciprocal transmission and opens a door towards the development of electronic isolators and circulators on silicon substrate.